Rethinking Agile Leadership: Digital Organizational Culture, Lecturer Agility, and Self-Reported Teaching Performance - Elvi Rahmi; Rike Ifriadi; Eka Eramahi Eramahi; Satriani Satriani; Ismiati Ismiati (Management of Education: Jurnal Manajemen Pendidikan Islam, 2026)
Digital transformation in universities requires organizational conditions that enable lecturers to respond to changing pedagogical demands. This cross-sectional study examined whether lecturers’ perceptions of agile leadership and digital organizational culture were associated with lecturer agility and self-reported teaching performance, and whether lecturer agility mediated these relationships. Data were collected from 112 permanent lecturers at eight universities in West Sumatra and analyzed using partial least squares structural equation modeling. Digital organizational culture was positively associated with lecturer agility (β = .484, p < .001) and self-reported teaching performance (β = .451, p < .001). Agile leadership was not significantly associated with lecturer agility (β = .167, p = .055) or self-reported teaching performance (β = .113, p = .279), whereas lecturer agility was unrelated to performance (β = .013, p = .915). No significant indirect effects were identified. The model explained 28.0% of the variance in lecturer agility and 23.5% of the variance in self-reported teaching performance. Digital organizational culture therefore emerged as the most consistent perceived contextual factor in this sample. These findings provide context-specific explanatory evidence rather than causal or broadly generalizable conclusions.